Contrast on leadership approaches: an empirical study of majority and minority Muslims - Khaliq, Ahmad (Malaysian Institute of Management, 2015)
Islamic leadership is a psychological contract between a leader and his followers where he will try his best to guide them, to protect them, and to treat them fairly and with justice. The objective of Islamic leadership principles is to encourage Muslim followers to practice and develop human qualities for a better place in a society and a better life for the Muslim Ummah.